Snake Bite: First Aid & Homoeopathic Approach in Critical Situations (Homoeopathy for All, 2026)
Snake bite is the very common problem faced in rural area. Treatment for snake bite includes giving antivenom therapy. Although many people are not aware about the success rate in treating in hospital because of so many myths in the society. With Homoeopathy, we can reduce the fatality and first aid as an immediate measure. Snakes are carnivorous reptiles of the suborder serpents. There are more than 3500 species of snake, but only 250 are venomous. Common Krait is the most common venomous snake. Our nation accounts for half the total number of deaths in the world due to snake bite. Snake bites are common in rural areas, poor communities, agricultural workers, fisherman and hunters. In the total snake population eighty percent of them are non-poisonous. Venom is saliva of snake. The enzymatic components present in snake venom cause local and systemic effects, and non enzymatic components provide lethality. The concentration of venom manifests diurnal and seasonal variation. Bites caused at night and after hibernation are the most fatal. Venoms advance in the body through superficial veins and lymphatics.
Keywords: Snakebite, First Aid, Envenomation, Homeopathy, Emergency Care, Integrative Approach.